2016
DOI: 10.18632/oncotarget.9602
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutics-induced Oct4 expression contributes to drug resistance and tumor recurrence in bladder cancer

Abstract: Cancer cells initially characterized as sensitive to chemotherapy may acquire resistance to chemotherapy and lead to tumor recurrence through the expansion of drug-resistant population. Acquisition of drug resistance to conventional chemotherapy is a major obstacle in the treatment of recurrent cancer. Here we investigated whether anticancer drugs induced Oct4 expression, thereby contributing to acquired drug resistance and tumor recurrence in bladder cancer. We identified a positive correlation of Oct4 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…5 In addition, chemotherapeutics can induce multidrug resistance, leading to treatment failure upon recurrence of the disease. 6,7 Some plant extracts have shown interesting anticancer properties without the serious side effects of cytotoxic agents. Among them, curcumin (CUR), which has anti-inflammatory activities, has also shown activity against cancer through multiple mechanisms, including inhibition of initiation, progression, invasion and metastasis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, chemotherapeutics can induce multidrug resistance, leading to treatment failure upon recurrence of the disease. 6,7 Some plant extracts have shown interesting anticancer properties without the serious side effects of cytotoxic agents. Among them, curcumin (CUR), which has anti-inflammatory activities, has also shown activity against cancer through multiple mechanisms, including inhibition of initiation, progression, invasion and metastasis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These result further indicate the importance of OCT4 contributing to the development of cancers in a number of ways (18,19). The aim of the present study was to investigate the role of miR-145 in the modulation of cervical cancer cell radiosensitivity, using transfection with miR-145 mimics to upregulate miR-145 in cervical cancer tera cells.…”
Section: Microrna-145 Sensitizes Cervical Cancer Cells To Low-dose Irmentioning
confidence: 91%
“…The results indicated that both HepG2 and Huh7 cells expressed lower levels of EpCAM when cultured in a 2D manner, whereas EpCAM expression was significantly higher in cells cultured on cellulosic scaffolds ( Figure 4B). 26,27 Oct4 expression was examined in HCC cells grown in the 2D system and on the cellulosic scaffolds by Western blot analysis. 26,27 Oct4 expression was examined in HCC cells grown in the 2D system and on the cellulosic scaffolds by Western blot analysis.…”
Section: Hcc Cell Spheroids Show Resistance To Chemotherapy In Vitromentioning
confidence: 99%